A level shifted asymmetric duty cycle controlled half-bridge series resonant LED driver configuration. Issue 2 (2nd April 2020) - D, Mounika; N, Vishwanathan; S, Porpandiselvi
ABSTRACT: This paper proposes an efficient LED lamp converter circuit incorporating dimming feature and multiple lamp independent control. The converter consists of a half-bridge resonant converter in series with a DC source. This converter operates at 200 kHz. Soft switching is employed with resonant power conversion. With modulation of the low frequency pulse width, the dimming feature is incorporated. The proposed configuration provides lower voltage stress for switching devices as well as lower switching losses resulting in increased efficiency. It is possible to independently control the current of each lamp. For two lamps operating in parallel with a total power of 25 W, a laboratory prototype has been designed. It can be used in residential applications. The proposed circuit is presented with detailed operation of the circuit, simulation and experimental results.